Problems and contradictions in the constitution of a southern european metropolitan area: Catania - Luca Ruggiero (European Regional Science Association (ERSA), 2001)
The Metropolitan Area of Catania has been created with a Regional law of 1986 (together with that of Palermo and Messina). With its 27 municipalities and for its characteristics it resembles, more than any other area in Sicily, a Metropolitan Area (MA), that is, a complex urban system in continuos evolution and at an advanced stage of the urban life cycle. However, it is still possible to trace some incongruous elements in the creation of such a system: a) the decentralisation process of function and activities, with respect to the main urban core, is at a very early stage; b) the main urban core still has difficulties to attract highly technological tertiary activities and strategic services which would allow a connection between the local, the national and the global level; c) the medium and small size centres have a low functional specialisation and are identified by highly hierarchical relationships; d) the MA has a weak cohesion in terms of economic and functional relations. The ambiguity of the relationships among the different centres, their low level of specialisation and the strong hierarchical dependency of the peripheral ones represent an obstacle to the creation of the Metropolitan Government of the area of Catania. This appears as a top down manoeuvre without solid territorial basis and with persistence of contradictory elements in the development and consolidation of the MA. This does not mean that a system to govern the MA would not be necessary to strengthen the evolution of Catania urban complex. This evolution has, in fact, known a clear intensification in the last ten years and has shown how urgent it is for this Government to realise socio-economic, infrastructural and cultural policies capable of accelerating the ongoing process. It is also essential for this Government to make its choices without incorporating automatically the power of local autonomies, but by reaching agreements on common issues.
Keywords: 330